Arrival of invasive pests in our direct environment and control opportunities - Zsigó, György (Acta Agraria Debreceniensis, 2015)
The author refers about the nowadays applied practical plant protection activities against pests occuring on trees, shrubs and turfs of public domains. It is overviewed those insects, diseases and weeds which cause damages and touched also upon disturbing the local residents only and tasks to the plant protection engineer expert to manage them. Among the special features of public domains should be mentioned that the rules are difficult to harmonize according to the legal, public health, and horticulture requirements at the same time. The anti-pesticide attitude of EU and the modest range of pesticides which are applicable on public domains make difficulties in optimal management work. The author draws up proposals how to manage the complex plant protection on public domains.